Inclusive design requirement in designing accessibility for low cognitive users - Nur Rahmah Zulkifli,; Noraidah Sahari @ Ashaari,; Nor Azan Mat Zin,; Rosadah Abdul Majid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In recent years, there has been extensive research on applying gamification in learning applications. However, there is little published information on the accessibility of gamification learning applications. Accessibility is essential for disabled users to access the application. There is a general lack of empirical research investigating the requirements of gamification applications for low cognitive users. Few studies have described the impact of limitations low cognitive users face with accessibility that distress their learning process. This study attempt to design learning gamification application for low cognitive user. Based on the requirement needs of low cognitive user, the application design was implemented and tested. Usability testing results showed positive feedback from implementing accessibility requirements in learning gamification applications.